Frame Score, Grazing and Delayed Feedlot Entry Effect on Performance and Economics of Beef Steers from Small- and Large-Framed Cows in an Integrated Crop-Livestock System - Songul Şentürklü; Douglas Landblom; Steven Paisley; Cheryl Wachenheim; Robert Maddock (Animals, 2021)
When selling small-framed steers at weaning, profitability is diminished. The hypothesis is that by using a vertically integrated business model that includes retained ownership, extended grazing, abbreviated feedlot finishing, and selling at slaughter, profitability would increase. Crossbred yearling steers (n = 288) from small size Aberdeen Angus (Lowline) × Red Angus × Angus × Angus cows and moderate to large size Red Angus × Angus × Simmental × Gelbvieh cows calved May−June were randomly assigned (complete randomized design), in a 3 y study, to feedlot control (FLT) and extended grazing (GRZ) frame score treatment groups. Mean frame score for FLT were small frame (SF) 3.82 and large frame (LF) 5.63, and for GRZ, SF: 3.77 and LF: 5.53. Least-square means were utilized to identify levels of effects and to control family-wise error adjusted with Tukey test. The FLT control steers were housed in the feedlot and fed growing diets and subsequently high energy corn-based diets for 218 days. The GRZ steers grazed a sequence of forages (native range, field pea-barley mix, and unharvested corn) for 212 days and then were transferred to the feedlot and fed high energy corn-based finishing diets for 82 days. The SF GRZ steers grew more slowly grazing native range and annual forages compared to GRZ LF steers, but SF steer grazing cost per kg of gain was reduced 7.80%. Grazing steers did not grow to their full genetic potential. Slower growth during grazing allowed LF and SF steers to grow structurally before feedlot entry creating a compensatory feedlot finishing growth response. Overall, grazing steer performance exceeded steer performance of the FLT control treatment and LF grazing steers had the highest rate of gain, and lowest feed cost per kg of gain. The GRZ steer feedlot days on feed were reduced 136 days and total feed intake was reduced resulting in LF and SF grazing steer feed cost reductions of 175.9 and 165.3%, respectively. Extended grazing also resulted in LF and SF grazing steer hot carcass weights to be greater than control LF and SF steers and SF grazing steers had greater dressing percent, and marbling score. Carcass quality grade, meat tenderness, and cooking losses were similar. System net returns were highest for LF (USD 911.58), and SF (USD 866.61) grazing steers. Managerial modification combining retained ownership, extended grazing, and delayed feedlot entry increased profitability and eliminated market bias.